COGNITIVE-BASED DEVELOPMENT OF SPOKEN ENGLISH SKILLS IN HIGH SCHOOL EDUCATION - Anora Nasimovna Ismailova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Developing strong speaking skills in English is essential for high school students as they prepare for academic and real-world communication. This paper looks at how using a cognitive approach helps develop spoken English by focusing on mental actions like attention and memory. These given insights offer practical ways to improve spoken English instruction, helping students gain confidence and competence in communication.